Preliminary Screening of Antimicrobial Properties of Few Medicinal Plants - S. Karthikeyan, K. M. Gothandam*, R. Aishwarya (Journal of Phytology, 2010)
Crude extracts were prepared from the leaves of ten medicinal plants viz., Alpinia galanga, Artabotrys uncinatus, Commelina benghalensis, Costus igneus, Euphorbia cyathopora, Justicia gendarussa, Kalanchoe pinnata, Panicum antidotale, Sauropus androgynous and Hibiscus using methanol as solvent and screened for their antibacterial activity against ten bacterial pathogens. The tested gram positive bacterial strains were Bacillus cerus, Bacillus megaterium, Micrococcus leuteus, Staphylococcus aureus, Streptococcus lactis, and gram negative strains were Pseudomonas aeruginosa, Escherichia coli, Enterobacter aerogenes, Klebsiella pneumoniae and Salmonella typhimurium. Among the ten plants tested, the methanol extracts of Alpinia galanga, Artabotrys uncinatus, Costus igneus and Yellow Hibiscus exhibited higher antibacterial activity when compared to the other plant extracts. These four plant extracts were further used for the phytochemical analysis. Results of the phytochemical analysis indicated the presence of alkaloids, phenolic compounds and flavanoids. The antibacterial activities of the leaves were due to the presence of various secondary metabolites